Mouse and human phenotypes indicate a critical conserved role for ERK2 signaling in neural crest development - Jason M. Newbern; Jian Zhong; Rasika S. Wickramasinghe; Xiaoyan Li; Yaohong Wu; Ivy S. Samuels; Natalie A. Cherosky; J. Colleen Karlo; Brianne O'Loughlin; Jamie C. Wikenheiser; Madhusudhana Gargesha; Yong Qiu Doughman; et al. (2008)
Disrupted ERK1/2 (MAPK3/MAPK1) MAPK signaling has been associated with several developmental syndromes in humans; however, mutations in ERK1 or ERK2 have not been described. We demonstrate haplo-insufficient ERK2 expression in patients with a novel approximately 1 Mb micro-deletion in distal 22q11.2, a region that includes ERK2. These patients exhibit conotruncal and craniofacial anomalies that arise from perturbation of neural crest development and exhibit defects comparable to the DiGeorge syndrome spectrum. Remarkably, these defects are replicated in mice by conditional inactivation of ERK2 in the developing neural crest. Inactivation of upstream elements of the ERK cascade (B-Raf and C-Raf, MEK1 and MEK2) or a downstream effector, the transcription factor serum response factor resulted in analogous developmental defects. Our findings demonstrate that mammalian neural crest development is critically dependent on a RAF/MEK/ERK/serum response factor signaling pathway and suggest that the craniofacial and cardiac outflow tract defects observed in patients with a distal 22q11.2 micro-deletion are explained by deficiencies in neural crest autonomous ERK2 signaling.